Bali Local Wisdom in Balinese Short Story Collection "Manyonyo" by Luh Suwita Utami: Literature Anthropology Study - Tanjung Turaeni, Ni Nyoman (International Journal of Psychosocial Rehabilitation, 2020)
Beside as a medium of entertainment, literary works also contain cultural values that provide positive value for the reader. Balinese short stories collection "Manyonyo" by Luh Suwita Utami carries the theme of local wisdom of the Balinese people. Therefore, the problem discussed in this research is how the values of local wisdom are described in the short story. The approach used is the literary anthropology approach assisted with a qualitative description method. The data source of this research is a Balinese short story collection "Manyonyo". From the twelve stories in the short story collection, two stories were selected as sources of research data, namely Manyonyo and Bhatara Da Tonta. Through the anthropological approach of literature, the results of the study show that the value of local wisdom of the Balinese people in the short story contains the concept of Tri Hita Karana, namely human relations with God, human relations with nature and human relationships with others.